Utilization of Whole Exome Sequencing Data to Identify Clinically Relevant Pharmacogenomic Variants in Pediatric Inflammatory Bowel Disease. Issue 12 (1st December 2020) - Mulder, Daniel J.; Khalouei, Sam; Warner, Neil; Gonzaga-Jauregui, Claudia; Church, Peter C.; Walters, Thomas D.; Ramani, Arun K.; Griffiths, Anne M.; Cohn, Iris; Muise, Aleixo M.
Abstract : INTRODUCTION: We hypothesized that variants within clinically relevant pharmacogenes could be identified using a whole exome sequencing data set derived from a cohort of more than 1, 000 patients with inflammatory bowel disease (IBD). METHODS: Pediatric patients diagnosed with IBD underwent whole exome sequencing. We selected 18 genes with supporting literature where specific exonic variants would influence clinical care. RESULTS: We identified actionable pharmacogenomic variants in 63% of patients. Importantly, 5% of patients with IBD were at risk for serious adverse effects from anesthesia and 3% were at increased risk for thrombosis. DISCUSSION: We identified exonic variants in most of our patients with IBD that directly impact clinical care.